A record of the little-known Bornean Ferret Badger Melogale everetti at Gunung Alap, Sabah, Malaysia - Anna Wong; Nurul Saadah Mohamed; Yit, Fred Yu Tuh; Wilting, Andreas (IUCN SSC Small Carnivore Specialist Group, 2011)
The Bornean Ferret Badger Melogale everetti is one of the least known Bornean carnivores, currently classified as Data Deficient on The IUCN Red List of Threatened Species. No Southeast Asian carnivore has a smaller known distribution. Few confirmed records from the last decade exist. One was captured in a wire mesh live-trap baited with banana, at Gunung (Mount) Alab, Crocker Range Park, Sabah, Malaysia, in October 2010.